Designing the use of solar panels to operate water pumps in groundwater use - Yoʻlchiyev M,E; Muhammadyoqubov Shodiyor Olmosbek o ‘g ‘li; Raxmatullayev Shamsiddin Hakimboy o ‘g ‘li (Лучшие интеллектуальные исследования, 2024)
Abstract: In this article, regions, underground, artesian basin, resource, hydrogeological works in arid regions of Uzbekistan, rational use and effectiveness of underground water collectors, monitoring. Issues of their protection are organized and analyzed.